SIGMA - A Malaysian signatures' database - Ahmad S.M.S.; Shakil A.; Ahmad A.R.; Agil M.; Balbed M.; Anwar R.Md. (2023)
This poster presents a database of Malaysian signatures named SIGMA describing the strategies adopted in compiling it and its technical details. The database consists of over 6,000 genuine signature samples and over 2,000 forged signature samples of Malaysian nationals. The signature samples are collected simultaneously in both online and offline mode thereby eliminating the variation which is inevitable if the two modes are done at different times. This is particularly appealing to studies which are aimed at exploring the co-relationships between static signature features and their dynamic counterparts (that are derived from offline and online signature samples respectively). Furthermore, all forgeries in the database are 'skilled forgeries'. The collection of only Malaysian signatures makes the database very useful for designing a signature verification system that is optimized to verify Malaysian signatures. 2008 IEEE.